2013
DOI: 10.1103/physreve.88.022204
|View full text |Cite
|
Sign up to set email alerts
|

Local stresses in the Janssen granular column

Abstract: We study experimentally the distribution of local stresses in a granular material confined inside a vertical cylinder. We use an image correlation technique to measure the displacement field of the container induced by the forces exerted by the grains on the inner wall. We describe an optimization procedure based on the linear theory of elastic shells to deduce the distribution of these forces from the measured displacement field. They correspond to the stress field of the granular material close to the contai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…shows that L c depends also on the grain size d which is not a parameter of the model so far because the granular mater is assumed to be continuous in the derivation of the shear stress, Eq. (2), in agreement with experiments for d/2R 0.1 [43,44]. Therefore, neither the grain size nor the rigidity of the cylinder affect the stress distribution in the regimes considered here [43,44].…”
Section: Figure 3(d)supporting
confidence: 88%
See 2 more Smart Citations
“…shows that L c depends also on the grain size d which is not a parameter of the model so far because the granular mater is assumed to be continuous in the derivation of the shear stress, Eq. (2), in agreement with experiments for d/2R 0.1 [43,44]. Therefore, neither the grain size nor the rigidity of the cylinder affect the stress distribution in the regimes considered here [43,44].…”
Section: Figure 3(d)supporting
confidence: 88%
“…0.1 [43,44]. Therefore, neither the grain size nor the rigidity of the cylinder affect the stress distribution in the regimes considered here [43,44].…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In order to solve it, constant b was assumed to be equal to 1. Constant B * 1 was computed using the characteristic values of our experiments, i.e., D = 3 mm, d = d 50 = 0.225 mm (the latter value obtained by SEM), and we assumed that µ s = tan(32 o ), κ ≈ 0.5, and c 0 ≈ 0.55 [1,24]. Additionally, we assumed θ ≤ 5 o .…”
Section: Stability Analysismentioning
confidence: 99%
“…Although the packing column confined in a container can also act as a simple but valid experimental system to test many theoretical models for the repartition or the transmission of stresses in granular materials [22][23][24][25], the mechanical behavior of the packing of granular chains did not receive enough attention until Brown et al revealed that a stress response in granular chains was very distinct from common grains, namely individual grains [26]. They found that strain stiffening occurred in the packing of long chains due to the inter-chains entanglements, which are absent in the packing system of individual grains or short chains.…”
Section: Introductionmentioning
confidence: 99%